The association between mobility limitations and physical performance measures in community-dwelling elderly: a cross-sectional study - Kaewjoho, Chonticha; Maharan, Sinthuporn; Khamnon , Narongsak (Archives of Allied Health Sciences, 2025)
Effective management of mobility limitations in older adults requires two key components: early identification of at-risk individuals and the ability to target the most critical underlying physical deficits. While numerous clinical tests for balance and strength exist, there is a lack of clarity on which measure best serves both these screening and prescriptive purposes. This study aimed to (1) describe age-group differences, (2) examine bivariate associations between SPPB and flexibility/balance/strength measures, and (3) identify independent predictors and explained variance via stepwise multiple linear regression with age and sex as covariates. This cross-sectional study included 108 older adults (mean age 71.0 ± 5.0 years; 67 women, 41 men) with mobility limitations (SPPB score ≤ 9). Flexibility was measured with the sit-and-reach test; balance by the functional reach test (FRT), single-leg stance test (SLST), timed up and go test (TUGT), and y-balance test (YBT); and strength by handgrip dynamometry. Pearson correlations identified bivariate associations with SPPB score. Stepwise multiple regression was used to determine which measures were most strongly and independently associated with mobility limitation. Although no significant differences were observed between sexes, SPPB scores were significantly lower among the older age groups (75–84 and ≥85 years) compared with the youngest group (p-value < 0.01). The FRT demonstrated the strongest correlation with SPPB (r = 0.37–0.67, p-value < 0.01). In Model 1, FRT alone accounted for 48.3% of the variance in SPPB (β = 0.695, p-value < 0.01). When age was added in Model 2, the explained variance increased slightly to 49.3% (ΔR² = 0.01; β = 0.143, p-value < 0.05). Functional reach emerged as a strong, independent predictor of mobility limitation, explaining nearly half the variance in SPPB score. Its simplicity and feasibility make it a valuable tool for routine geriatric screening to identify older adults at greatest risk of mobility decline. Age provides a modest but significant contribution. These findings support the incorporation of quick, practical balance assessments (FRT) in both community and clinical practice. The cross-sectional design limits causal inference, and findings may not be applicable to institutionalized populations.